Stability and Regularity of Suitably Weak Solutions of n-dimensional Magnetohydrodynamics Equations (Journal of Partial Differential Equations, 2003)
" In this paper, it is shown that the weak solutions of magnetohydrodynamics equations in spaces L^q(R^+; L^p(R^n)) are stable and regular."
Keywords: Stability; regularity; magnetohydrodynamics equations